Pengaruh Kepuasan Kerja dan Komitmen Organisasi pada Turnover Intention - Susiani, Vera (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
Turnover intention is an employee behavior that determine the performance of a company. The high rate of turnover intention will be a serious problem for the company. This study was conducted to provide advice and solutions to the company to reduce the turnover rate from the perspective of job satisfaction and organizational commitment. The study was conducted at the Stones Entertainment Center located in Kuta, Bali. The population is 80 people. The method used is the census so that the sample in this study is 80 people. The analysis technique used is path analysis. Based on the results , job satisfaction has a positive effect on organizational commitment, job satisfaction negatively impact to turnover intention, and organizational commitment has negative effect on turnover i ntention. Keywords : turnover intention, job satisfaction, organizational commitment